Utility of Clinical Biomarkers to Predict Central Line-associated Bloodstream Infections After Congenital Heart Surgery. Issue 3 (March 2015) - Shin, Andrew Y.; Jin, Bo; Hao, Shiying; Hu, Zhongkai; Sutherland, Scott; McCammond, Amy; Axelrod, David; Sharek, Paul; Roth, Stephen J.; Ling, Xuefeng Bruce
Abstract : Background: Central line-associated bloodstream infections is an important contributor of morbidity and mortality in children recovering from congenital heart surgery. The reliability of commonly used biomarkers to differentiate these patients has not been specifically studied. Methods: This was a retrospective cohort study in a university-affiliated children's hospital examining all patients with congenital or acquired heart disease admitted to the cardiovascular intensive care unit after cardiac surgery who underwent evaluation for a catheter-associated bloodstream infection. Results: Among 1260 cardiac surgeries performed, 451 encounters underwent an infection evaluation postoperatively. Twenty-five instances of central line-associated blood stream infections (CLABSI) and 227 instances of a negative infection evaluation were the subject of analysis. Patients with CLABSI tended to be younger (1.34 vs. 4.56 years, P = 0.011) and underwent more complex surgery (RACHS-1 score 3.79 vs. 3.04, P = 0.039). The 2 groups were indistinguishable in white blood cell, polymorphonuclears and band count at the time of their presentation. On multivariate analysis, CLABSI was associated with fever (adjusted odds ratio: 4.78; 95% CI: 1.6–5.8) and elevated C-reactive protein (CRP; adjusted odds ratio: 1.28; 95% CI: 1.09–1.68) after adjusting for differences between the 2 groups. Receiver-operating characteristic analysis demonstrated the discriminatory power of both fever and CRP (area under curve 0.7247, 95% CI: 0.42 to 0.74 and 0.58, 95% CI: 0.4208 to 0.7408). We calculated multilevel likelihood ratios for a spectrum of temperature and CRP values. Conclusions: We found commonly used serum biomarkers such as fever and CRP not to be helpful discriminators in patients after congenital heart surgery. Abstract : Supplemental Digital Content is available in the text.